2019
DOI: 10.22435/kespro.v10i1.1711
|View full text |Cite
|
Sign up to set email alerts
|

Situasi Human Immunodeficiency Virus-Tuberkulosis Di Kabupaten Merauke 2018: Ancaman Pada Umur Produktif

Abstract: Abstract Background: Pulmonary tuberculosis is the most serious opportunistic infection in HIV/AIDS subjects and is a major cause of mortality and morbidity in developing countries. Objective: To describe  the results of HIV / TB examination in Merauke District Hospital Method: Study design is cross-sectional using data from “Studi evaluasi deteksi kasus TBC dengan alat tes cepat molekuler di Indonesia tahun 2018”. Descriptive data analysis is applied based on secondary data of PLWHA patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…17 Similarly, one study showed that HIV coinfection among TB patients was higher in Merauke General Local Hospital, Papua, than in other study areas in Indonesia. 18 Bali and DIY were among the lower TB-risk provinces, and it may be linked to less intensive case finding and reporting. In that sense, the coverage of TB programs to diagnose cases in the population and notify them into the available TB surveillance system is less than what the program had targeted.…”
Section: Discussionmentioning
confidence: 99%
“…17 Similarly, one study showed that HIV coinfection among TB patients was higher in Merauke General Local Hospital, Papua, than in other study areas in Indonesia. 18 Bali and DIY were among the lower TB-risk provinces, and it may be linked to less intensive case finding and reporting. In that sense, the coverage of TB programs to diagnose cases in the population and notify them into the available TB surveillance system is less than what the program had targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating the variance component estimator using the maximum likelihood method produces a biased estimator so that the estimation of the variance component is better using the restricted maximum likelihood (REML) method. REML possibility function is as follows [12] [13]:…”
Section: Linear Mixed Modelmentioning
confidence: 99%
“…According to a World Health Organization (WHO) report, HIV-Tuberculosis (TB) fatalities contribute over 1.3 million deaths worldwide. HIV and TB weaken the patient's immune system, which reduce life expectancy [13]. External variables like unemployment and poverty also have an impact on HIV prevalence [14].…”
Section: Introductionmentioning
confidence: 99%